The Status of Mathematical Inventory Theory - Veinott, Arthur F. (Management Science, 1966)
This paper surveys the current status of mathematical inventory theory. The review is limited to studies which seek optimal policies for dynamic inventory models. Models with certain and uncertain demands are discussed. Particular attention is focused on multi-item and/or multi-echelon inventory systems.